An Endoparasitic Wasp, Diachasmimorpha longicaudata (Ashmead) (Insecta: Hymenoptera: Braconidae) - C. R. Thompson (EDIS)
Diachasmimorpha (formerly Biosteres or Opius) longicaudata Ashmead (Wharton 1987) is a solitary braconid wasp parasitoid of Caribbean fruit fly, Anastrepha suspensa (Loew), larvae. This document is EENY-193 (originally published as DPI Entomology Circular 325), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2001. Revised: November 2004.